Engaging the organizational field: The case of project practices in a construction firm to contribute to an emerging economy. Issue 5 (July 2021) - Narayanan, V.K.; Huemann, Martina
Highlights: We profile the micro activities of project managers of a major Indian construction firm. These managers, in coordination with their senior management, undertook numerous field building activities that were crucial for their projects' success, but these activities simultaneously addressed major gaps in the economic infrastructure of India. For example, labor and supplier markets in India were underdeveloped, and the projects had to bear the cost of this development. Thus, our data portray these construction industry managers as active participants in India's economic transition. Abstract: We develop a model of practices undertaken by project managers to address the challenges of organizational fields in an emerging economy context. We anchor the model in a qualitative study of project managers' activities in a major construction industry firm in India. We make three contributions. First, our study illustrates how the micro activities of project managers, in coordination with the actions of senior management, address the emerging economy challenges, and project managers' responses hold lessons for the emerging literature on "projects as practice." Second, we augment the dominant cognitive orientation in the discussion of organizational fields in project management literature with a practice perspective. Finally, we enrich the institutional theory stream in project management. In addition to the mechanisms identified in that stream of literature, our data suggest that the activities of project managers in major construction projects may act as a mechanism of transition in emerging economies. While the project managers in the Indian construction industry firm undertook numerous field building activities that were crucial for their projects' success, these activities were simultaneously addressing major gaps in the economic infrastructure of India. Thus, our data portray construction industry managers as not merely engaged in project execution, but as active participants in the economic transition of a country. Similarly, labor and supplier markets in India were underdeveloped, and the projects had to bear the cost of this development.